2021
DOI: 10.3892/etm.2021.10575
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with intra‑stent restenosis after percutaneous coronary intervention

Abstract: The present study aimed to explore the correlations between clinical, biological, imagistic and procedural factors with the risk of intra-stent restenosis (ISR) in coronary artery disease (CAD) patients after percutaneous coronary intervention (PCI). An observational cross-sectional study was conducted in a high-volume PCI center over a period of 2 years. A total of 235 consecutive patients diagnosed with angina or acute coronary syndrome treated by PCI were included in the study. Diagnosis of ISR was document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…These results were comparable to the previous studies. [11,12] We found that 40 (48.2%) patients were smokers. Mean LDL cholesterol of the patients was 68.6±1.97 mg/dl and mean uric acid was 6.2±2.35 mg/dl.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These results were comparable to the previous studies. [11,12] We found that 40 (48.2%) patients were smokers. Mean LDL cholesterol of the patients was 68.6±1.97 mg/dl and mean uric acid was 6.2±2.35 mg/dl.…”
Section: Discussionmentioning
confidence: 74%
“…Our results showed that the stents longer than 30mm were associated with a higher incidence of In-Stent Restenosis (p=0.03). [11,12] Active pharmacologic medication, stent plat shape, and drug carrier are the three main components of a drug eluting stent that contribute to its efficacy. Within the first 30 days after artery injury, newer DES designs allow for the controlled release of medicines that are anti-inflammatory, immunological modulatory, and/or antiproliferative at the site of injury.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, classic cardiovascular risk factors are deemed to increase the likelihood of ISR ( 9 , 10 ), but in some others this relationship is not very clearly validated ( 11 ). Many studies investigated the role of various cardiovascular risk factors in the development of restenosis; diabetes mellitus was incriminated in many researches as an independent risk factor for ISR, along with arterial hypertension, active smoking and low-density lipoprotein cholesterol (LDL-C) ( 12 14 ). Erkan Yıldırım et al ( 15 ) showed in multivariate logistic regression that ISR was independently associated with Gensini score, stent diameter and length, left ventricle ejection fraction, and LDL-C.…”
Section: Introductionmentioning
confidence: 99%
“…It is a minimally invasive surgical procedure, i.e., using a catheter to place a stent to open up the narrowed blood vessel [ 4 , 5 ]. However, post-treatment with PCI is frequently followed by vascular wall injury leading to inflammation, thrombosis, and finally restenosis (re-narrowing of the treated blood vessel) [ 6 , 7 ]. Thus, restenosis after PCI is the main problem that limits the long-term success of the PCI.…”
Section: Introductionmentioning
confidence: 99%
“…This allows the stable arrest of platelets, platelet activation, and irreversible platelet aggregation leading to thrombus growth [ 9 ]. Growth factors released from activated platelets promote vascular smooth muscle cell (SMC) proliferation and migration from the media to the intima, causing a thickening of the intimal vessel wall layer, called intimal hyperplasia, which restricts the luminal blood flow causing instent restenosis [ 6 , 7 , 10 , 11 , 12 , 13 ]. Thus, binding the platelet GPIb-V-IX complex to vWF is crucial for early platelet adherence to the damaged vessel wall.…”
Section: Introductionmentioning
confidence: 99%